Problems of agricultural production in the context of european integration processes - Butenko, Ye.; Volontyr, A.; Vovna, M.; Prykhodko, M. (Land Management, Cadastre and Land Monitoring, 2025)
The article studies problems of Ukraine in the sphere of agricultural production within the framework of the European integration process. The state of agrarian production potential and the land fund of Ukraine is assessed. The indicators of agro-industrial production of agricultural products in Ukraine and its separate region (Kirovograd region) are described. A comparative analysis of the number of economic entities, volumes of crop and livestock production for 2021 (pre-war period) and 2022 (post-war period) in the context of Ukraine and Kirovohrad region based on the materials of the State Statistics Service is carried out to assess Ukraine’s capabilities and competitiveness in the foreign market. The article describes the problems of the decline in agricultural production and estimates the losses of agricultural production since the beginning of the full-scale invasion. The article analyses Ukraine’s foreign trade with the EU countries and Ukraine’s actions on the way to European integration. The state of agricultural land in Kirovohrad region is assessed, the main negative factors of agricultural development of the territories in the pre-war period are described. The ways to restore agricultural land as a result of the existing problems are described. The state of the soil cover affected by the hostilities is assessed. The principles and requirements for exporting products to the EU market are described. The problems of the agricultural sector of Ukraine in the production of products for the foreign market are analyzed and the measures to be taken to join the European Union are described. The article analyses the prospects that the European Union receives from Ukraine’s membership and the prospects of Ukraine if it is granted the status of a member of the European Union. The necessity of accelerating Ukraine’s European integration process is substantiated. Key words: agricultural production, agricultural products, agricultural land, European integration processes.